Laparoscopic management of acute abdominal emergencies. Issue 9 (September 2022) - Farkas, Nicholas; Singh, Rishabh; Scala, Andrea
Abstract: Use of minimally invasive approaches to acute abdominal surgical emergencies has increased in recent decades. Uptake has been slower than for elective surgery, however, with concerns regarding inadvertent injury and operative time being most frequently cited. Laparoscopy for abdominal pain has shown to be safe and is a useful diagnostic procedure in the context of unexplained abdominal pain. Minimally invasive surgery has also been shown to be the approach of choice in appendicitis and cholecystitis. Laparoscopy has shown to be useful in trauma patients and may obviate the need for laparotomy. Management of perforated peptic ulcers has shown to be feasible and safe, with some uncertainty as to the superiority over an open approach. The management of perforated diverticulitis has been the subject of much debate, with significant risk possibly associated with minimally invasive lavage. Small bowel obstruction may also be managed using laparoscopy but the potential for inadvertent injury remains. While useful and certainly yielding benefits in terms of postoperative recovery when performed without incident, the decision to proceed minimally invasively in many acute abdominal emergencies must be taken by clinicians and surgical teams with suitable experience and expertise.